1938
DOI: 10.1103/physrev.53.318
|View full text |Cite
|
Sign up to set email alerts
|

A New Method of Measuring Nuclear Magnetic Moment

Abstract: To apply these ideas a beam of molecules in a 'Z state (no electronic moment) is spread by an inhomogeneous magnetic field and refocused onto a detector by a subsequent field, somewhat as in the experiment of Kellogg, Rabi and Zacharias. ' As in that experiment the reorienting

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
279
0
17

Year Published

1966
1966
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 636 publications
(312 citation statements)
references
References 3 publications
0
279
0
17
Order By: Relevance
“…Numerous measurements of magnetic moments of neutral atoms have been performed using the Rabitechnique [4]: A Stern-Gerlach force acting on an atomic beam in an inhomogeneous magnetic field separates different spin states in space. Transitions between different Zeeman substates are induced in a homogeneous magnetic field region and are monitored by a deflection in a second inhomogeneous B-field.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous measurements of magnetic moments of neutral atoms have been performed using the Rabitechnique [4]: A Stern-Gerlach force acting on an atomic beam in an inhomogeneous magnetic field separates different spin states in space. Transitions between different Zeeman substates are induced in a homogeneous magnetic field region and are monitored by a deflection in a second inhomogeneous B-field.…”
Section: Introductionmentioning
confidence: 99%
“…Stern and Gerlach (Gerlach, 1922) proved that the electron-magnetic moment of an atom in an external magnetic field originates only in certain directions in the experiment in 1922. Uhlenbek and Goudsmit found that the connection between the magnetic moment and spin angular momentum of electron (Uhlenbek, 1925), Rabi and Breit found the transition between the energy levels in oscillating magnetic field (Rabi, 1938). This also proved to be observed in the event of the first magnetic resonance.…”
Section: Magnetic Resonancementioning
confidence: 93%
“…This period is called Rabi period, with ω R being the Rabi frequency, as these equations were derived on the basis of the so-called rotating wave approximation by Rabi (1937) (see also Rabi et al (1938)) in the context of early nuclear magnetic resonance experiments (in beams, with a magnetic dipole transition matrix element V , of course).…”
Section: Quantum Dynamics Of Spectroscopic Transitionsmentioning
confidence: 99%